If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4(x + -5) = 3 + 4x + -19 Reorder the terms: 2x + -4(-5 + x) = 3 + 4x + -19 2x + (-5 * -4 + x * -4) = 3 + 4x + -19 2x + (20 + -4x) = 3 + 4x + -19 Reorder the terms: 20 + 2x + -4x = 3 + 4x + -19 Combine like terms: 2x + -4x = -2x 20 + -2x = 3 + 4x + -19 Reorder the terms: 20 + -2x = 3 + -19 + 4x Combine like terms: 3 + -19 = -16 20 + -2x = -16 + 4x Solving 20 + -2x = -16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 20 + -2x + -4x = -16 + 4x + -4x Combine like terms: -2x + -4x = -6x 20 + -6x = -16 + 4x + -4x Combine like terms: 4x + -4x = 0 20 + -6x = -16 + 0 20 + -6x = -16 Add '-20' to each side of the equation. 20 + -20 + -6x = -16 + -20 Combine like terms: 20 + -20 = 0 0 + -6x = -16 + -20 -6x = -16 + -20 Combine like terms: -16 + -20 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| 7.5(x-4)=-0.5x+18 | | (9x-1)(3x+9)=0 | | 3(1/4)p=2(1/2) | | 6(x-1)+46=-2x | | -6.5(4p+6)-1.4(3p-5)=0 | | 50+4y-22=13y-14-3y | | (31/4)p=21/2 | | 1/5n=12 | | -3-(5-5p)=0 | | -3(-2*x+4)-(x-6)=y | | f(m)=20-0.25m | | 69-5x=4x+18 | | 3y-10=5x+22 | | x^2=-13 | | -17x-20=-14x+70 | | -7/3(y-12)-1/6y=0 | | 3/4x-3/2=6 | | -7/3(y-12)-1/6y | | 4x+9=3x+17 | | 3x+7=2x+15 | | 5x^3/2-35=100 | | -177=9*n | | 11x-3=3x+21 | | 9x+18=27 | | 5x-35=100 | | 6x-5=31-2x | | 24-3x=56+2x | | 3x-4(7x+3)=5x+7(9x-10) | | 5.59+55.9=111.8 | | -17-(-40)=x/2 | | X=2(-2)+6 | | X*13-110=x*6-12 |